2016
DOI: 10.1098/rsos.150517
|View full text |Cite
|
Sign up to set email alerts
|

A model of muscle atrophy based on live microscopy of muscle remodelling inDrosophilametamorphosis

Abstract: Genes controlling muscle size and survival play important roles in muscle wasting diseases. In Drosophila melanogaster metamorphosis, larval abdominal muscles undergo two developmental fates. While a doomed population is eliminated by cell death, another persistent group is remodelled and survives into adulthood. To identify and characterize genes involved in the development of remodelled muscles, we devised a workflow consisting of in vivo imaging, targeted gene perturbation and quantitative image analysis. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 47 publications
(56 reference statements)
2
21
0
Order By: Relevance
“…During metamorphosis, changes in IOM cell size and myofibril content have been noted (Kuleesha et al, 2014, 2016). We previously showed that wildtype IOMs undergo dramatic cortical and membrane remodeling with costamere integrin adhesion complex disassembly and reassembly at discrete pupal stages (Ribeiro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…During metamorphosis, changes in IOM cell size and myofibril content have been noted (Kuleesha et al, 2014, 2016). We previously showed that wildtype IOMs undergo dramatic cortical and membrane remodeling with costamere integrin adhesion complex disassembly and reassembly at discrete pupal stages (Ribeiro et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to TOR TED , Rm62-RNAi induced histolysis occurred 15 hours later and did not delay histolysis of DEOMs. In the context of abdominal muscles, TOR TED did not exactly behave like a dominant negative version of the endogenous TOR protein since TOR-RNAi mainly affected cell size and had negligible effects on cell survival [30]. We can only speculate that the regulation of cell survival and cell growth are mediated by different protein complexes.…”
Section: Discussionmentioning
confidence: 89%
“…Since TOR TED is a potent inducer of autophagy in the fat body [41], activation of autophagy may trigger cell death of wildtype DEOMs and TOR TED overexpressing DIOMs. In a parallel study, we found that RNAi of 5 autophagy related genes (Atg5, Atg9, Atg12, Atg17, and Atg18) caused inhibition of atrophy during the remodeling of DIOMs [30]. We examined 25 time-lapse datasets of pupae expressing shRNAs against Atg9 (7) and Atg5, Atg12 and Atg18 (6 each).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations